저장 공간과 검색 효율을 위한 XML 문서의 RDB 스키마 모델 - 권훈(Hoon Kwon); 김정희(Jeong-Hee Kim); 곽호영(Ho-Young Kwak) (한국콘텐츠학회 논문지, 6(4), 2006)
XML instances for purpose of information exchange are normally stored in the legacy relational database. Therefore, integrations with relational database are required for effective XML applications. To support these requirements, virtual decomposition storage or decomposition storage methods which save separates structures of instances to relational database have researched. However, these storage methods contain different information of schema structure and layers which has caused difficulties to process query during search operation as well as increased overheads due to duplicate savings for separate storages. Therefore, in this research, additional field of 'Eltype' has introduced to previous database schema structure to instance and schema structure, provide consistent level information and propose storage structure to map each field to schema field of relational database. As results, XML instance and structures can be stored together to minimize overheads and required storage-space. Also, synchronized storage layer structure provides easier processing of search query. 정보 교환을 위한 XML 인스턴스는 일반적으로 legacy한 관계형 데이터베이스에 저장되어 있기 때문에 효율적인 XML 응용을 위한 데이터베이스와의 연동이 요구 되었으며, 이러한 요구를 지원하기 위하여 인스턴스와 스키마 구조를 분리하여 관계형 데이터베이스에 저장하는 가상 분할 저장 또는 분할 저장 방식의 인스턴스 저장 모델들이 연구되어지고 있다. 그러나 이러한 저장 방식은 인스턴스 구조와 인스턴스간의 계층 정보가 불일치하여 검색 시 질의 처리를 어렵게 하고 있고, 또한 분리 저장에 따른 중복 데이터들의 존재로 저장 시 오버헤드가 높아진다. 따라서 본 논문에서는 XML문서를 저장할 때, 기존 연구의 데이터베이스 스키마 구조에 Eltype이라는 필드를 추가하여 인스턴스와 스키마의 상이한 계층 정보를 동일화하고, 저장 구조 각각의 필드를 관계형 데이터베이스 스키마 필드와 일치되는 저장 구조를 제안하였다. 그 결과 XML 인스턴스와 스키마 구조간의 저장이 가능하게 되어 중복 저장에 따른 오버헤드 및 저장 공간 감소, 그리고 동일화된 저장 계층 구조로 인해 검색 질의 처리가 쉬워졌다.